Madīnat az-Zahrāʾ, Spanien. Die Arbeiten des Jahres 2017 - Arnold, Felix (e-Forschungsberichte des DAI, 2017)
Madīnat az-Zahrāʾ was the capital of the 10th century Umayyad caliphate in al-Andalus and is today one of the most important sites of Islamic culture in the west. A new project is dedicated to the investigation of the Plaza de Armas, the main public square of the caliphal city. The aim of the first season of field work was the investigation of the Great Portico, which delimits the Plaza de Armas in the west and forms the façade of the caliphal palace. The building history of the portico was clarified, as well as the reconstruction of the portico based on building elements found during the excavation of the portico in 1975. In addition, a geophysical survey was conducted in the area to the east of the Plaza de Armas, in order to study the eastern limit of the plaza. The dimension and structure of several buildings could be determined. In addition a geomagnetic survey was conducted in the garden area of the palace.